Arsitektur Masjid Sebagai Perpaduan Estetika dan Fungsionalitas - rosyid, bilqis syifaur (Maliki Interdisciplinary Journal, 2024)
Islam is a religion that also embraces art, especially in the realm of architecture. Islamic architecture is inextricably linked to the cultural tapestry of Islam around the world. It represents the concrete manifestation of human endeavor in fulfilling the spiritual and physical needs of both Muslims and non-Muslims. Mosque architecture embodies a harmonious blend of aesthetics and functionality, reflecting the profound values of the Islamic faith, culture, and civilization. Preserving mosque architecture falls upon the shoulders of the present generation, ensuring the safeguarding of this invaluable cultural and historical heritage.